Educational Games for Children with Down Syndrome - extended abstract - Zdravkova, Katerina (Universidad de La Rioja, 2020)
In the last 10 years, the incidence of Down syndrome increased worldwide. In order to improve the quality of life of these children, and to increase their life expectancy, many systematic measures have been undertaken. Inclusive education, which embraces educational, social and emotional practises, based on well-structured instruction, interventions and support in the classroom is definitely one of them. In parallel with the in-class activities, educational software stimulates the inclusion. This paper presents the recommendations how to create such educational applications together with the pilot study intended to develop literacy skills, basic mathematical competencies and memory. A small Android application was created and presented to children attending the recently open Day Care Centre for Down syndrome (DCCDS) in Skopje. The enthusiasm and interest to use the application is the greatest motivation to carry on with the study, to create more ambitious applications and after an approval by the experts and parents to offer them to the all the children in the country. The application can be easily adapted to all languages, making it available to much wider community.
Keywords: Basic learning skills; Down syndrome; Educational games; Inclusive education; Preparation for independent life